THE INFLUENCE OF PROMOTION, PRICE AND PRODUCT QUALITY ON THE PURCHASE DECISION OF HONDA MOTOR PARTS (CASE STUDY IN AHASS HONDA INTI MOTOR DEPOK) - bhaskara, Bhaskara Damar Djarkasih; Fenny B.N.L. Tobing; Ganda T. Hutapea (Fundamental Management Journal, 2024)
Ahass Honda Inti Motor is a company engaged in the motorcycle repair shop (spare parts service, spare parts and others). This dealership was built to be a solution to the many motorcycle dealers around Depok that have not been officially standardized. but according to the comparison and consideration for consumers. However, this dealer has several problems, such as consumers around Depok who prefer to service at unofficial dealers, even though in terms of spare parts security, it is the official dealer who has a better level of security. The variables used in this research study are Promotion (X1), Price (X2) and Product Quality (X3) and indicators of customer satisfaction are the main things studied. This research has a quantitative type and the data is processed using Rank Spearman. A total of 52 people were respondents in this research study. The research findings state that the effect of promotion on purchasing decisions is due to the rcount results being more than rtable. And there is a price effect on purchasing decisions because rcount is greater than rtable. There is a Quality Effect on Purchasing Decisions because the rcount value is more than the rtable. Key Words: Promotion, Price, Product Quality and Purchasing Decision